Genesis and source of Permian natural gas in well Qiatan-1 of piedmont depression, southwestern Tarim Basin - Li HUANG; Ying ZHAO; Huixian LÜ; Xiaomin XIE; Li LI; Qilin XIAO; Zhanghu WANG; Guo CHEN; Qiang MENG (Shiyou shiyan dizhi)
Recently, a significant breakthrough in natural gas exploration was achieved in well Qiatan-1 in the Permian carbonate strata of the Western Tianshan thrust belt in the piedmont depression of southwestern Tarim Basin, marking the discovery of a new exploration layer in the area. However, this region is characterized by multiple sets of source rocks and extremely complex sedimentary and structural features. Research on the genesis and source of the natural gas in well Qiatan-1 is insufficient, restricting its further natural gas exploration. Therefore, the study systematically investigated the genesis and source of the natural gas in well Qiatan-1 based on regional geological background, geochemical characteristics of the gas, and potential source rock features. The measured results showed that the natural gas in well Qiatan-1 was mainly composed of methane (83.53%), with a gas dryness coefficient (C1/C1-5) of 0.992, and contained relatively high levels of N2 (8.36%), CO2 (7.28%), and He (0.110%). The carbon isotope values of methane, ethane, propane, and CO2 in the gas were -27.8‰, -20.2‰, -18.4‰, and 1.7‰, respectively. Based on the natural gas composition and alkane carbon/hydrogen isotope composition, the natural gas in well Qiatan-1 was determined to be coal-type gas in the high to over-mature stage. Considering the distribution, organic matter abundance, type, thermal maturity of its potential source rocks, the gas in this well was mainly sourced from Permian source rocks in the Permian Qipan Formation, and may also be mixed with a small amount of carbon isotopes, forming heavier inorganic hydrocarbon gases. In addition, the components and isotopic evidence of non-hydrocarbon gases such as N2, CO2, and He showed that a certain proportion of inorganic gas had mixed into the natural gas in well Qiatan-1. The helium isotopic composition suggested that the proportion of mantle-derived helium was about 14.6%, and the He content had reached the standard for helium-rich natural gas (He ≥ 0.100%).